Retrofuturismo do processo em animação - Carvalho, Duarte Filipe Neves (2021)
This project has the objective of showing the interaction between new and old animation methods in the production of one animation. The use of new and classical processes isn’t only limited to the physical part of the project but also to the conceptual part. This use of both processes is visible across in theme, story, character and environmental design, among others. As so, all the steps towards the making of the animation are described here. This document that goes along with the animation is divided in main themes: State of the art, The three themes, Pre-production, Production and Post-production. All these themes, except State of the art, consist in the analysis and decomposition of the steps of production. The state of the art, shows what at this time, is made in the field of animation nationally in Portugal and internationally, dividing these into academic, independent animation and industry animation. The three themes are about the appearance of the initial ideas, what are the reasons for the choice of the one developed, and the reasons for the rejections of the others, taking into account time constraints and the connection with the retrofuturism theme. The section of Pre-production has the intention to clarify the whole initial phase of production, identification of cinema genre, the showing and the choice behind all the visual elements that make the animation’s world, production of a storyboard, and the making of an animatic, that makes up a mockup of the animation essential to the whole production. The Production section explains what’s the methodology behind the production, and all the technical knowledge necessary to the making of this animation. Post-production is the section that explains the last steps that consist of the final assembly of the animation